No evidence for sex bias in winter inter‐site movements in an Arctic‐nesting goose population. (2nd March 2015) - Weegman, Mitch D.; Fox, Anthony D.; Bearhop, Stuart; Hilton, Geoff M.; Walsh, Alyn J.; Cleasby, Ian R.; Hodgson, David J.
Abstract : Understanding movement of individuals between sites is necessary to quantify emigration and immigration, yet previous analyses exploring sex biases in site fidelity among birds have not evaluated remigration (the return of marked birds that moved to alternative areas from the site at which they were marked). Using novel Bayesian multistate models, we tested whether between‐winter emigration, remigration and survival rates were sex‐biased among 851 Greenland White‐fronted Geese Anser albifrons flavirostris marked at Wexford, Ireland. We found no evidence for sex biases in emigration, remigration or survival. Thus, sex biases in winter site fidelity do not occur in any form in this population; these techniques for modelling sex‐biased movement will be useful for a better understanding of site fidelity and connectivity in other marked animal populations.